The quest for material gain and engaging in risky sexual behaviour by young girls : a study in Sunnyside, Pretoria - Jacob, Geraldine Elaine (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.